Oculomotor impairments in de novo Parkinson’s disease - Zhou, Meng-Xi; Wang, Qin; Lin, Yin; Xu, Qian; Wu, Li; Chen, Ya-Jing; Jiang, Yu-Han; He, Qing; Zhao, Lei; Dong, You-Rong; Liu, Jian-Ren; Chen, Wei (Frontiers in Aging Neuroscience, 2022)
Objective: Reliable electrophysiological indicators are urgently needed in the precise evaluation of Parkinson's disease (PD). It is still elusive whether oculomotor performance is impaired or has clinical value in early PD. This study aims to explore oculomotor performance in newly diagnosed, drug-naïve PD and its correlation with clinical phenotype. Methods: 75 patients with de novo PD, 75 patients with essential tremor(ET), and 46 gender- and age-matched healthy controls (HCs) were included in this cross-sectional study. All subjects underwent oculomotor test via videonystagmography (VNG). Visually guided saccade (VGS) latency, saccadic accuracy and gain in smooth pursuit eye movement (SPEM) at three frequencies of the horizontal axis were compared among the three groups. Patients with PD also received detailed motor and non-motor evaluation by serial scales. The association between key oculomotor parameters and clinical phenotypes were explored in PD patients. Results: Both de novo PD and ET patients showed prolonged saccadic latency and decreased saccadic accuracy relative to HCs. SPEM gain in PD was uniformly reduced at each frequency. SPEM gain at 0.4 Hz was also decreased in ET compared with HCs. However, there was no significant difference of oculomotor parameters between de novo PD and ET patients. Furthermore, prolonged saccadic latency was correlated with long disease duration, whereas decreased SPEM gain was associated with severe motor symptoms in de novo PD patients. Conclusions: Ocular movements are impaired in de novo, drug naïve PD patients; these changes could be indicators for disease progression in PD.